Foot pressure analysis of the grab, track and kick start techniques in swimming - Tatar, Y.; Uzun, S.; Ramazanoglu, N.; Sayli, Ö.; Piskintas, B.; Gercek, N.; Sanli, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The goal of swimming race is to complete the required distance in the least amount of time. Swimmers start performance is vital to win the race. The purpose of the current study was to investigate plantar pressure values and start performance parameters for grab, track, and kick-start techniques from the Omega OSB11 starting block. Method: Nineteen male from the Turkish national swimming team (age 16.84 ± 1.68 years, height 179.9 ± 5.8 cm, body mass 57.9 ± 7.1 kg) volunteered to participate in this study. The Swimmers were instructed to perform three different start techniques (grab, tract and kick start) and finish the start performance at 15-m distance. The participants completed a warm up similar to their prerace routine and they performed two trials for each start technique. Trials were recorded with two digital video cameras. Start efficiency times were recorded by a touchpad positioned at 15 m distance from starting block and electronic time system (Omega, ARES21, Switzerland) for grab-start, track-start and kick-start techniques. Foot plantar pressure data were collected using an F-Scan VersaTek wireless system (Tekscan, Inc. South Boston, MA) during three different start techniques. Prior to data collection F-scan sensors (model: 3000E; resolution: 3.9 sensors/cm2) were calibrated and data was taken with the 100 Hz sampling rate. Peak and average pressure data were analyzed by using the F-Scan Mobile Research software. Results: Statistical comparisons were made among plantar pressure values of three different start techniques and also15 m swimming performance using one-way ANNOVA. The average and peak foot pressure values (N/cm2) were significantly lower for kick-start position (mean:12,68±2,3; peak: 16,45±3,4;) than both tract (mean:16,58±3,4; peak: 21,0±3,7) and grab-start (mean:19,42±2,8; peak: 23,58±4) positions (p=0.00) during push of phase in the front leg. Similarly, the average and peak foot pressure values were significantly less for kick-start position than both tract and grap-start positions (p=0.00) during push of phase in the rear leg. Altough, there were no significant differences in time to 15m, distance of entrance among swimming start techniques, kick start technique was faster and also resulted in longer distance of entry than the other start techniques (p>0,05). Discussion: At kick start technique, although the foot pressure was lower than the other start techniques during push off phase, distance of entry was longer and the time of the 15 m swimming is shorter. However, this study results are conflifting with another study. Slowson SE et al. (2013) stated that swimmers generating higher than average peak forces were more likely to produce a better overall start performance. In our study, low levels of average peak pressure resulted in better start performance. Future works should be applied to explain relationship between foot pressure, block time, distance of entry and muscle strength.